Crossing borders, facing barriers: a rights-based narrative review of HIV care access among African migrants living with HIV - Joanne Ellen Mantell; Tsitsi B. Masvawure; Noelle Anna Thomas; Yael Hirsch-Moverman; Gavin George (Frontiers in Public Health, 2026)
International migration has long shaped economies and public health. In today’s globalized world, migrant health is increasingly a critical equity issue. This narrative review focuses on healthcare access for international migrants from sub-Saharan Africa who are living with HIV. We address the question: “How do legal, policy, and socio-structural factors influence access to HIV care for African migrants, and what rights-based strategies can ensure health equity for this population?” We synthesize peer-reviewed and grey literature (2005–early 2025) using the Availability, Accessibility, Acceptability, and Quality (AAAQ) human rights framework integrated with a structural violence (SV) lens. We find that African migrants living with HIV encounter considerable systemic barriers to care driven by restrictive immigration policies, fragmented and exclusionary health financing, intersecting stigmas (racism, xenophobia, HIV stigma, homophobia), and inconsistent provider competencies. We recommend seven bold, yet actionable, strategies to align policy and practice with states’ human rights obligations: decoupling healthcare from immigration enforcement, tapping migrant community power, creating centralized migrant-inclusive health information systems, re-imagining migrant-inclusive universal healthcare, shared financial responsibility for migrant health, operationalizing ethical safeguards to protect the healthcare rights of migrants and recognition of the needs of uniquely situated migrants, particularly women, youth, and LGBTQI+ individuals.